Fiscal Space for Infrastructure Borrowing in South-Eastern Europe : A Suggested Approach - World Bank (Washington, DC, 2014)
The seven countries of South Eastern Europe (Albania, Bosnia and Herzegovina, Bulgaria, Croatia, FYR Macedonia, Romania, and Serbia and Montenegro) are in the process of transition, undertaking significant fiscal adjustment as they seek to move to a path of sustainable growth. Previous high debt has been reduced and/or restructured for most countries, which have committed to a path of fiscal responsibility as one of the key ingredients in the recovery process. Fiscal consolidation is also necessary in order to prepare the ground for future entry into the European Union (EU), including for being in a position to incur expenditures arising from the obligations of future EU membership. A significant amount of new borrowing for infrastructure investment is being contemplated by these countries, often based on bilateral and multilateral funding. This short approach paper seeks to set out the key issues that will need to be kept in mind when evaluating the proposed borrowing and investments. While the note is indicative, and needs to be supplemented by more detailed analysis by each Government, it suggests that caution needs to be exercised in any new borrowing. To the extent that capital expenditure is financed by loans from international institutions and partners, the same word of caution applies to them in their infrastructure lending to the countries of South Eastern Europe.